PLL to the Rescue: A Novel EM Fault Countermeasure - Miura, Noriyuki (2016)
Electromagnetic injection (EMI) is a powerful and precise technique for fault injection in modern ICs. This intentional fault can be utilized to steal secret information hidden inside of ICs. Unlike laser fault injection, tedious package decapsulation is not needed for EMI, which reduces an attacker's cost and thus causes a serious information security threat. In this paper, a PLL-based sensor circuit is proposed to detect EMI reactively on chip. A fully automatic design flow is devised to integrate the proposed sensor together with a cryptographic processor. A high fault detection coverage and a small hardware overhead are demonstrated experimentally on an FPGA platform.